The Role and Prospects of Big Data and Artificial Intelligence in the Construction of Smart Cities - Mo, Yunru (Journal of Theory and Practice of Management Science, 2025)
As a new form of modern urban development, smart cities have achieved comprehensive perception, ubiquitous interconnection, intelligent integration, and sustainable innovation of cities through the deep integration of cutting-edge technologies such as information technology, Internet of Things, big data, cloud computing, and artificial intelligence. This article explores the key roles of big data and artificial intelligence in the construction of smart cities, analyzes how they can change the management mode of cities and the lifestyle of residents, and looks forward to future development trends. Through the research in this article, it is expected to provide useful theoretical support and practical guidance for the sustainable development of smart cities.